Faulty posture: Prevalence and its relationship with Body Mass Index and Physical Activity among female adolescents - Golalizadeh Dina; Toopchizadeh Vahideh; Farshbaf-Khalili Azizeh; Salekzamani Yaghoub; Dolatkhah Neda; Pirani Ali (Sciendo, 2020)
Study aim: The aim of this study was to determine the prevalence of postural disorders and their associated risk factors among high school girls in the city of Tabriz, Iran.